Otologic complications of temporomandibular joint arthrocentesis due to arteriovenous fistula - Joseph A. Fanti; Abhita Reddy; Evan Greenbaum; Mohammed Qaisi; Biraj Shah; James Murphy (Clinical Case Reports, 2022)
Abstract Arteriovenous fistula (AVF) is a rare sequela following arthrocentesis of the temporomandibular joint. This case report discusses a constellation of symptoms, findings, and appropriate management of a patient with a superficial temporal AVF. Several findings in this case, including vertigo, nystagmus, and hearing loss, have not been previously documented in the literature.